SIMBOL AGAMA DAN ORGANISASI TRANSNASIONAL: LIWA’ DAN RAYAH DALAM BENDERA HIZBUT TAHRIR INDONESIA - Dani Habibi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This article aims to reveal the hermeneutical meaning behind the flags Liwa and Rayah. The two flags by Hizbu Tahrir Indonesia (HTI) are seen as the flag of the Prophet. However, this view was denied by other Islamic groups because the flags of Liwa and Rayah were the flags used by Taqiyyudin An-Nabhani when declaring the government of Khilfah Islamiyah. Flags Liwa and Rayah black and white, which Black called Rayah and white called Liwa'. The two flags read Laa illaaha illaa Allah Muhammad Rasul Allah. In making interpretations, the author uses Paul Ricoeur's hermeneutical theory. The interpretation debate is heating up when Hizbu Tahrir wants to replace the Pancasila ideology into the ideology of the Caliphate. The difference in interpretation, point of view and context of hadith is the main problem why researchers want to reinterpret. The hermeneutic approach according to researchers is appropriate if it is used for the method of interpreting hadith texts and religious symbols. This research includes qualitative research. Qualitative research is a type of library research that collects data from books, books, and journals. The results of this study are symbols in the HTI flag that have ideological and political movements. In this study, the flag symbol turned out to be a symbol of identity which led to the Islamic political movement. the movements and practices carried out by HTI are nothing but the change of the democratic system and the ideology of the Pancasila into the ideology of the Islamic Shari'a with the Khilafah Islamiyah system Abstrak Artikel ini bertujuan untuk mengungkap makna hermeneutis di balik bendera Liwa dan Rayah. Kedua bendera tersebut oleh Hizbut Tahrir Indonesia dipandang sebagai bendera rasulullah. Namun pandangan tersebut dibantah oleh kelompok Islam lainya karena bendera liwa dan rayah adalah bendera yang digunakan oleh Taqiyyudin An-Nabhani ketika mendeklarasikan sistem pemerintahan Khilfah Islamiyah. Bendera liwa dan rayah berwarna hitam dan putih, yang Hitam dinamakan Rayah dan putih dinamakan Liwa’. Kedua bendera tersebut bertulisan Laa illaaha illaa Allah Muhammad Rasul Allah. Dalam melakukan interpretasi, penulis menggunakan teori hermeneutika Paul Ricoeur.. Perbedaan penafsiran, sudut pandang dan konteks hadis menjadi masalah utama kenapa peneliti ingin menafsirkan kembali. Pendekatan hermeneutika menurut peneliti sesuai jika digunakan untuk metode menafsirakan teks hadis dan simbol-simbol keagamaan. Penelitian ini termasuk penelitian kualitatif. Penelitian kualitatif jenis penelitian pustaka yang mengumpulkan data-data dari kitab, buku, dan jurnal. Adapun hasil dari penelitian ini adalah simbol dalam bendera HTI mempunyai makna ideologi dan gerakan politik. Dalam penelitian ini, simbol bendera tersebut ternyata sebagai lambang identitas yang berujung pada gerakan politik Islam. gerakan dan praktek yang dilakukan oleh HTI tidak lain adalah mengangganti sistem demokrasi dan ideologi Pancasila menjadi ideologi syari’at Islam dengan sistem pemerintahan Khilafah Islamiyah